A Study on the Credit Rating Analysis Based on Apartment Big-Data - et. al., Seung-Yeon Hwang, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
With the rapid progress of the fourth industrial revolution recently, related technologies such as IoT, AI and Big-Data have developed innovatively and various kinds of big data are being generated in various fields. In particular, various studies using such big data are underway in the financial sector. Domestic and foreign fintech companies and financial institutions have applied big data and related technologies to credit rating and are making various efforts to expand and apply from traditional to new credit rating methods. Therefore, in this paper, we want to present guide information on the development of new credit rating model, such as carrying out credit rating analysis using apartment big data and visualizing the results so that we can understand them intuitively.